Peptide Synthetase Gene in Trichoderma virens - Wilhite, S. E. (American Society for Microbiology, 2001)
Trichoderma virens (synonym, Gliocladium virens), a deuteromycete fungus, suppresses soilborne plant diseases caused by a number of fungi and is used as a biocontrol agent. Several traits that may contribute to the antagonistic interactions of T. virens with disease-causing fungi involve the production of peptide metabolites (e.g., the antibiotic gliotoxin and siderophores used for iron acquisition). We cloned a 5,056-bp partial cDNA encoding a putative peptide synthetase (Psy1) from T. virens using conserved motifs found within the adenylate domain of peptide synthetases. Sequence similarities with conserved motifs of the adenylation domain, acyl transfer, and two condensation domains support identification of the Psy1 gene as a gene that encodes a peptide synthetase. Disruption of the native Psy1 gene through gene replacement was used to identify the function of this gene. Psy1 disruptants produced normal amounts of gliotoxin but grew poorly under low-iron conditions, suggesting that Psy1 plays a role in siderophore production. Psy1 disruptants cannot produce the major T. virens siderophore dimerum acid, a dipetide of acylated N(δ)-hydroxyornithine. Biocontrol activity against damping-off diseases caused by Pythium ultimum and Rhizoctonia solani was not reduced by the Psy1 disruption, suggesting that iron competition through dimerum acid production does not contribute significantly to disease suppression activity under the conditions used.